UNA NUEVA ESPECIE DE Shevtchenkella (ACARI, PROSTIGMATA, ERIOPHYIDAE) DE ARGENTINA - Ballari, Maria Celeste; de Quinteros, Sara L. Quintana; Flechtmann, Carlos H. W. (REVISTA DE AGRICULTURA, 2013)
Shevtchenkella marceloi Flechtmann, n.sp. is described and figured from female, larva and nymph specimens, from Tessaria dodonaeifolia (Hook. y Arn.) Cabrera from Jujuy, Argentina. Remarks on Shevtchenkella species from South America are presented.